2022
DOI: 10.3390/catal12111345
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of Iron Ore@Biomass Derived ESBC to Degrade Tetracycline Hydrochloride for Heterogeneous Persulfate Activation

Abstract: Iron-based catalysts are widely used in water treatment and environmental remediation due to their abundant content in nature and their ability to activate persulfate at room temperature. Here, eggshell biochar-loaded natural iron slag (IO@ESBC) was successfully synthesized to remove tetracycline hydrochloride (TCH) by activated persulfate. The morphology, structure and chemical composition of IO@ESBC were systematically characterized. The IO@ESBC/PS process showed good performance for TCH removal. The decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Wang et al investigated the treatment of coking wastewater via the α-MnO 2 /PMS process, and found that this catalytic treatment can significantly improve the biodegradability of wastewater [8]. Tian et al reported largescale synthesis of iron ore and biomass-derived biochar to activate the persulfate oxidation of tetracycline hydrochloride [9]. Additionally, Qi et al constructed a Bi 2 WO 6 /PMS system where carbamazepine could be efficiently degraded with the assistance of visible light irradiation [10].…”
mentioning
confidence: 99%
“…Wang et al investigated the treatment of coking wastewater via the α-MnO 2 /PMS process, and found that this catalytic treatment can significantly improve the biodegradability of wastewater [8]. Tian et al reported largescale synthesis of iron ore and biomass-derived biochar to activate the persulfate oxidation of tetracycline hydrochloride [9]. Additionally, Qi et al constructed a Bi 2 WO 6 /PMS system where carbamazepine could be efficiently degraded with the assistance of visible light irradiation [10].…”
mentioning
confidence: 99%